Common Medical Health Problems Among the Hospitalized Elderly Patient: A Cross Sectional Study (Journal of Dhaka National Medical College & Hospital, 2018)
Objective: To find out the common medical health problems among the hospitalized elderly patients Methodology: This was a cross sectional study conducted in a tertiary care hospital located in old Dhaka. 100 male and 100 female elderly patients were selected purposively from Medicine ward and health problems were evaluated by preformed questionnaire, bed side examination and some available investigations.Results: Anaemia, electrolyte imbalance, UTI, pneumonia, tuberculosis, malignancy, osteoarthritis, acute exacerbation of bronchial astma and COPD, stroke, uncontrolled hypertension, DM were the common diagnosis of elderly hospitalized patient in medicine ward.Conclusion: Proper care should be provided for elderly patient that can reduce the rate of hospitalization. Additionally, proper hospital facilities should be arranged for this group.J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 36-39